123k views
1 vote
Which expression represents the factored form of 6x2-13x-5?

User Wfoster
by
6.2k points

2 Answers

1 vote
the anwser would be (2x-5)(3x+1).
User Chris Conley
by
6.9k points
4 votes

Answer:

The factor form of the given equation is
6x^2-13x-5=(2x-5)(3x+1)

Explanation:

Given : Expression
6x^2-13x-5

To find : Which expression represents the factored form of given expression?

Solution :

We have given the quadratic equation,


6x^2-13x-5=0

We solve the given quadratic equation by middle term split,

i.e. the multiple of number is 30 and addition is -13,


6x^2-15x+2x-5=0

Taking common to form factor,


3x(2x-5)+1(2x-5)=0


(2x-5)(3x+1)=0

Therefore, The factor form of the given equation is
6x^2-13x-5=(2x-5)(3x+1)

User GILO
by
5.8k points